Anti-inflammatory, antioxidant and neuroprotective effects of niacin on mild traumatic brain injury in rats - KOYUNCUOĞLU, TÜRKAN; AKAKIN, DİLEK; ERZİK, CAN; YÜKSEL, MERAL; YEGEN, BERRAK (My University, 2023)
AIM: To study the effects of niacin, a water-soluble vitamin, on inflammation, oxidative stress and apoptotic processes observed after mild traumatic brain injury (TBI). MATERIAL and METHODS: A total of 25 Wistar albino male rats were randomly divided into control (n=9), TBI + Placebo group (n=9), TBI + niacin (500 mg/kg; n=7) groups. Mild TBI was performed under anesthesia by dropping a 300 g weight from a height of 1 meter onto the skull. Behavioral tests were applied before and 24 hours after TBI. Luminol and lucigenin levels and tissue cytokine levels were measured. Histopathological damage was scored in brain tissue. RESULTS: After mild TBI, luminol and lucigenin levels were increased (p<0.001), and their levels were decreased with niacin treatment (p<0.01-p<0.001). An increased score was obtained with trauma in the tail suspension test (p<0.01), showing depressive behavior. The number of entries to arms in Y-maze test were decreased in TBI group compared to pre-traumatic values (p<0.01), while discrimination (p<0.05) and recognition indices (p<0.05) in object recognition test were decreased with trauma, but niacin treatment did not change the outcomes in behavioral tests. Levels of the anti-inflammatory cytokine IL-10 were decreased with trauma, and increased with niacin treatment (p<0.05). The histological damage score was increased with trauma (p<0.001), and decreased with niacin treatment in the cortex (p<0.05), and hippocampal dentate gyrus region (p<0.01). CONCLUSION: Niacin treatment after mild TBI inhibited trauma-induced production of reactive oxygen derivatives and elevated the anti-inflammatory IL-10 level. Niacin treatment ameliorated the histopathologically evident damage.
Keywords: Tıp; Dahili Tıp Bilimleri; Nöroloji; Cerrahi Tıp Bilimleri; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Neurology; Surgery Medicine Sciences; Health Sciences; Klinik Tıp (MED); Klinik Tıp; CERRAHİ; KLİNİK NÖROLOJİ; Clinical Medicine (MED); CLINICAL MEDICINE; SURGERY; CLINICAL NEUROLOGY; Cerrahi; Nöroloji (klinik); Surgery; Neurology (clinical); Brain trauma; Neuroprotection; Niacin; Vitamin B3